Cardiobacterium hominis endocarditis associated with cerebral, renal, and splenic infarctions: A case report and review of the literature. (2023) - Kitagawa, Izumi; Ono, Ryohei; Tobe, Shunichi; Nagatsuka, Motoki
Abstract: Cardiobacterium hominis ( C. hominis ) is a fastidious, pleomorphic, gram-negative bacillus that causes infective endocarditis. Identification of C. hominis is difficult because it grows very slowly in culture media. C. hominis is also known to cause large friable vegetations in the heart valves, complicated by systemic embolism. Here, we report a case of C. hominis infective endocarditis associated with cerebral, renal, and splenic infarctions. A 58-year-old Japanese man with a medical history of diabetes mellitus presented with acute right-sided back pain. Enhanced abdominal computed tomography scan showed a right renal infarction and splenic embolism, and cerebral magnetic resonance imaging revealed multiple infarctions. Transesophageal echocardiography revealed the presence of a vegetation and severe aortic regurgitation. C. hominis was detected in the blood culture; thus, a diagnosis of C. hominis infective endocarditis was made. The patient received antibiotic therapy and surgical aortic valve replacement, and he was doing well without major complications. We also reviewed the cases of systemic emboli caused by C. hominis infective endocarditis. Highlights: C. hominis is known to cause heart valve vegetations complicated systemic emboli. C. hominis infective endocarditis presents with prolonged symptoms. Physicians should suspect concomitant complications in the presence of organ infarction.